THE EFFECTS OF WORK FROM HOME AND FLEXIBLE WORKING ARRANGEMENT ON EMPLOYEE PERFORMANCE DURING COVID-19 PANDEMIC - Arifin, Agus Zainul; Siswanto, Halim Putera; Kurniawan, Vincentius Kevin; Kristian, Michelle (International Journal of Application on Economics and Business, 2023)
The purpose of this study was to analyze the effects Work from Home (WFH) and Flexible Working Arrangement (FWA), with Work Motivation (MOT) moderation, on Employee Performance (EP). The research is quantitative research. The type of research used based on the research objective is explanatory research. The data analysis technique in this study used Partial Least Square (PLS). This study uses the two-factor theory of Frederick Herzberg. The results obtained that Work from Home has a positive and significant effect on Employee Performance. Work from Home has a positive and significant effect on Work Motivation. Flexible Working Arrangement has a positive and significant effect on Work Motivation. Flexible Working Arrangement has a positive and significant effect on Employee Performance. Work Motivation has a positive and significant effect on Employee Performance. Work from Home, with Work Motivation intervention, does not have a positive and significant effect on Employee Performance. Meanwhile, Flexible Working Arrangement with Work Motivation intervention, also does not have a positive and significant effect on Employee Performance. Flexible working arrangements can be selected by employees based on different work schedules to meet personal or family needs. Companies can adjust work as the new normal for employees who are still working from home to return to full-time work on a hybrid basis. It is important for companies to understand and develop work from home and flexible working arrangements to encourage productive behavior and prevent unproductive behavior considering the role of work motivation in influencing performance.